Faktor-Faktor Yang Mempengaruhi Kinerja Tenaga Kesehatan Di Rumah Sakit: Tinjauan Teoritis - Ida Ayu Laksmi Arnita Utari; Dety Mulyanti (Jurnal Kesehatan Amanah, 2023)
Performance is something that is very important and must be considered by all management, both at the level of small and large agencies. The performance of health workers is the result or level of success of a person as a whole in carrying out tasks compared to various possibilities, such as work standards, services to patients and targets or criteria that are in accordance with professional responsibilities. The purpose of this theoretical review is to find out how the factors that influence the performance of health workers in hospitals. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are factors that influence work performance or achievement, namely individual factors consisting of individual factors of effort (effort), abilities, and role/task perception. While environmental factors include physical condition, equipment, time, education and training. It can be concluded that the result or level of one's overall performance during a certain period is influenced by individual and environmental factors. Health workers also in carrying out their functions are not independent, but are related to job satisfaction and levels of pay, health workers also improve the quality of human resources need to continue to learn and hone skills and abilities as well as the need for Hospitals to evaluate the performance of health workers.